Analysis of Twitter Utilization as the Medium of Communication among Jersey Collector Community—Reds Army LFC - Putra, N G (KnE Social Sciences, 2018)
Reds Army LFC is the biggest community of original collector of Liverpool FC football jerseys in Indonesia. Initially, the Reds Army LFC was founded in 2010 as a Blackberry Messenger (BBM) group, with 30 members who had met on an online forum Kaskus.us (now Kaskus.co.id) from JABODETABEK. Through the aid of social media and the Internet, especially twitter, Reds Army LFC has grown to be a national jersey collector community that has more than 5000 members, coming from different provinces of Indonesia. The utilization of twitter by Reds Army LFC is very important and attracts the interests of the Researchers. Based on this phenomena, the researcher can say that ‘Analysis of Twitter Utilization as the Medium of Communication among Jersey Collector Community—Reds Army LFC’ is the fittest title for this research. This research has used a qualitative method. Participant observation, semi-structural interview, and literature studies were used as the method of data collectivity. The result of this research shows that twitter utilization as the medium of communication in Reds Army LFC has an impact, both between the members and even to the other people who do not have any relation to this community. Keywords: component, social media, Twitter, online community